Hematological and performance adaptations to altitude training (2,320 m) in elite middle-distance and distance swimmers - Mujika, I.; Bourdillon, N.; Zelenkova, I.; Vergnoux, F.; Millet, G. P. (Frontiers in Physiology, 2024)
Purpose: Elite swimmers often schedule altitude training camps ahead of major events in an attempt to maximize performance. However, the relationships between altitude-induced hematological changes, markers of training adaptation, and performance changes in such context are unclear. This study assessed hematological status, markers of daily adaptation, and swimming performance in elite middle-distance and distance swimmers during a 22-day altitude training camp at 2,320 m, 2 weeks prior to World Championship qualification competition.